The Effectiveness of Giving Iron Tablets and a Combination of Iron Tablets and Date Palm Juice on Increasing Hb Levels in Anemic Pregnant Women at Cigeulis and Picung Community Health Centers in 2025 - Sadiah Sadiah; Ai Solihah; Eris Meilani; Eva Febriyani; Yeyet Sulastri; Ratna Wulandari; Ageng Septa Rini (International Journal of Health Engineering and Technology, 2026)
Anemia during pregnancy is a condition in which pregnant women experience iron deficiency in the blood. The purpose of this study was to determine the effectiveness of administering iron tablets and a combination of iron tablets and date palm juice on increasing Hb levels in anemic pregnant women at Sobang and Picung Health Centers in 2025. Quantitative research method, quasi-experimental research design with control group design. Simple random sampling technique. The population was pregnant women, a sample of 30 people, 15 people as the control group (group 1) who were only given iron and 15 people as the intervention group (group 2) were given treatment by consuming iron and date palm juice every day for 7 days. The results of the univariate study showed that the educational characteristics of pregnant women were mostly low education (60%) and high education (40%). The results of the bivariate study obtained an average Hb level before being given iron tablets of 10.2267 and an average Hb level after being given iron tablets of 10.9333 and an average Hb level before being given a combination of iron tablets and date palm juice of 10.360 and an average Hb level after being given a combination of iron tablets and date palm juice of 11.253. Both groups of research results showed an increase in Hb levels but there was a comparison of the increase in Hb levels, so that giving a combination of iron tablets and date palm juice was more effective in increasing hemoglobin levels compared to those only given iron tablets. This may occur because there are differences in characteristics of pregnant women in Education. It is hoped that it can be used as a source of information for pregnant women to increase their insight and knowledge about anemia and anemia prevention in their pregnancy.